An Industrial systems design on New Miracle Candle Mfg. Corp. - Limpiada, Diane Marie Madel G.; Aspera, Romeo Isaiah M.; Garcia, Maeleen A.; Derit, Lea. (Diliman, Quezon City College of Engineering, 2005)
In today's ever changing world, a company must continually adapt in order to survive. To be responsive to these issues, the Company must be able to apply effective strategies. The aim of this paper is to assess New Miracle Candle Mfg. Corp.'s (heretofore referred to as the 'Company') present status with respect to its mission, vision, and goals and to generate strategies that will guide the Company in achieving them. After a thorough systems documentation and analysis using various tools such as PEST (Political, Economic, Social and Technological) Analysis, Porter's Five Forces (Rivalry, Buyer Power, Supplier Power, Threat of Entry/Barriers to Entry, and Threat of Substitutes) Analysis, and SWOT (Strengths, Weaknesses, Opportunities, and Threats), four priority strategies were identified and translated into operational recommendations. These are: 1) Cost Leadership, 2) Increasing Product Visibility, 3) Increasing Efficiency Through Low-Cost Techniques, and 4) Looking for Better Suppliers. Cost Leadership, which simply means being the lowest-cost supplier of products within acceptable quality standards, lead to recommendation of cost reduction through IMPROVED SOURCING/PROCUREMENT, INVENTORY MANAGEMENT, and EFFICIENCY MEASURES. Thus, three of the four strategies were already addressed by implementing the cost leadership strategy. Increasing product visibility, on the other hand, led to the recommendation of the INSTALLATION OF A WEBSITE, FINANCIAL-INDIVIDUAL INCENTIVE SCHEME FOR SALES REPRESENTATIVES, and the INSTALLATION OF A SALES OUTLET IN SM MEGAMALL. In consideration of the Company's limited resources, these recommendations were ranked in order to define recommendations that need to be prioritized. IMPROVED SOURCING/PROCUREMENT and INVENTORY MANAGEMENT ranked the highest with respect to criteria such as ease of implementation, results and required capital. Thus, these two must take precedence in the implementation. Implementation plans have been developed to assist the Company. IMPROVED SOURCING/PROCUREMENT is expected to reduce the costs of raw material acquisition but requires a capital of P 5 000.00 ? P 10 000.00 per E-bidding service. E-bidding is an auction-style bidding environment in the Internet provided as a service by BayanTrade. Cost of such service is considered minimal compared to the benefit of being able to look for the lowest-cost supplier. Being able to look for a supplier that offers a price of P 1.00 per kilo of paraffin wax than the Company's present supplier will translate to a savings of P190 000.00 per year. This savings amounts to 180.3% of the Company's net income for the year 2003. The implementation of the new procurement system is to be spearheaded by the Procurement Officer to be assigned by the Company. INVENTORY MANAGEMENT requires only the cost of salary paid to the employee in charge of monitoring the inventory. At minimum wage, this would only cost P 6 000.00/month. An additional employee may not even be needed because of the minimal workload the monitoring requires. This minimal cost leads to cost savings such as reduced inventory holding costs, ordering costs, and increased efficiency through minimization of stockout occurrence. An Inventory Officer should head the implementation of the system. This officer may be the same as the Production Manager. INSTALLATION OF A SALES OUTLET IN SM MEGAMALL requires a start-up capital of P 47 200.00 and a daily operating expense of P1 133.00. The Company needs to earn revenue minus cost of sales of P 37 923.33 per month to offset its operating expenses and recover the start-up capital within one year. This may seem quite large but this project is expected to increase the Company's profitability because the mall provides the visibility that the Company's products need. The Sales and Marketing Manager must oversee the installation of the sales outlet. The cost of the FINANCIAL-INDIVIDUAL INCENTIVE SCHEME for the Company's Sales Representatives will depend on the Company. This scheme is expected to increase the motivation of the sales representatives, which will later be translated into higher sales. The Sales and Marketing Manager is the one in charge of the implementation of this incentive scheme. INSTALLATION OF A WEBSITE requires a start-up capital ranging from P 2 000.00-P25 000.00. This start-up capital is only a one-time expense and is expected to increase Company's revenues through increased product visibility. The installation of the website may even open the door to exportation. The Sales and Marketing Manager should head the installation of the website. For greater detail on the EFFICIENCY Measures, please refer to Aquino, et al. A Methods Engineering Study on Miracle Candle Cottage Industries, 2nd sem AY 2002-2003. Prevailing conditions during the study were found to be applicable up to this moment.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: New Miracle Candle Manufacturing Corporation; Marketing channels--Management.; Delivery of goods--Management.; Industrial procurement; Materials management; System design